2019
DOI: 10.1371/journal.pone.0221199
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of concentrated herbal extract granules, YH1, as an add-on medication in poorly controlled type 2 diabetes: A randomized, double-blind, placebo-controlled pilot trial

Abstract: Background In Asian countries, many patients with type 2 diabetes fail to achieve controlled glycated hemoglobin (HbA 1c ) levels while taking several classes of oral hypoglycemic agents (OHAs). Traditional Chinese medicine could be an alternative therapeutic option for poorly controlled type 2 diabetes. YH1 is a concentrated Chinese herbal extract formula that combines Rhizoma Coptidis and Shen-Ling-Bai-Zhu-San. This randomized, double-blind, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 32 publications
4
26
0
Order By: Relevance
“…Shen-ling-bai-zhu-san (SLBZS) is a TCM which has been extensively used in China. SLBZS improves hypoglycemic action and β-cell function, offers protection against ulcerative colitis, and alleviates inflammation and non-alcoholic steatohepatitis-induced liver injury, [11][12][13]. Additionally, SLBZS can promote beneficial gut microbiota abundance [14].…”
Section: Introductionmentioning
confidence: 99%
“…Shen-ling-bai-zhu-san (SLBZS) is a TCM which has been extensively used in China. SLBZS improves hypoglycemic action and β-cell function, offers protection against ulcerative colitis, and alleviates inflammation and non-alcoholic steatohepatitis-induced liver injury, [11][12][13]. Additionally, SLBZS can promote beneficial gut microbiota abundance [14].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the safety concerns of RCEG, high-dose treatment for up to 60 weeks has been shown to be safe, without obvious hepatic or renal toxicity, which has previously been reported ( Huang et al, 2019 ). In this study, the range of RCEG in the high-dose group was between 0.08 and 0.23 g/kg/d, with a median of 0.14 g/kg/d ( Supplementary Material S2 ).…”
Section: Discussionmentioning
confidence: 73%
“…It is also possible that TCM doctors chose the low-dose RCEG to treat other symptoms instead of controlling the glycemic level. Importantly, a previous pilot clinical study reported that YH1, containing high-dose RCEG and SLBZS, can benefit patients with poorly controlled type 2 diabetes who have already been treated with three or more kinds of OHA ( Huang et al, 2019 ). After 3 months of YH1 add-on treatment, there were significant reductions in HbA1c and the lipid profile, as well as a significant increase in HOMA-β.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence also shows that adiponectin and adiponectin receptor signaling may have a key role in improving nonalcoholic fatty liver disease [31]. According to current research, Shenling Baizhu powder has significant lipid-lowering effects, improves insulin resistance, and reduces the accumulation of triglycerides in the liver [32,33]. To further reveal the mechanisms underlying the hepatocyte protective effects of SL, we used the CDAA diet to establish NAFLD rats, which is the most commonly used and reproducible nutritional model.…”
Section: Discussionmentioning
confidence: 99%